Effects of total flavonoids of sea buckthorn (Hippophae rhamnoides L.) on cytotoxicity of NK92-MI cells. (December 2017) - Hou, Diandong; Wang, Decheng; Ma, Xiande; Chen, Wenna; Guo, Shengnan; Guan, Hongquan
Sea buckthorn ( Hippophae rhamnoides L.) has multifarious medicinal properties including immunoregulatory effect. The total flavonoids of Hippophae rhamnoides L. (TFH) are the main active components isolated from berries of sea buckthorn. The aim of this study was to evaluate the effects of TFH on the cytotoxicity of NK92-MI cells and its possible mechanisms. NK92-MI cells were treated with TFH (2.5 or 5.0 mg/L) or phosphate-buffered saline (PBS) for 24 h, the cytotoxicity against K562 was detected by measuring the release of lactate dehydrogenase (LDH), expression levels of NCRs (NKp30, NKp44, NKp46) and NKG2D were detected by flow cytometry, and expression levels of perforin and granzyme B were detected by western blot. Cytokine Antibody Arrays with 80 cytokine proteins were used to profile the effect of TFH on cytokines. Western blot was adopted to detect the effects of TFH on STAT1, STAT4, and STAT5 signal pathway. Compared with the normal control group, TFH could significantly enhance NK92-MI cell cytotoxicity against K562 cells, upregulate expressions of NKp44, NKp46, perforin, and granzyme B. TFH could upregulate expressions of IL-1α, IL-2, IL-7, IL-15, CSF-2, CSF-3, MCP-1, MIG, IFN-γ, TNF-α, and TNF-β and downregulate expressions of IL-16, MIP-1β, CX3CL-1, and MIF. TFH could increase expressions of phospho-STAT1 and phospho-STAT5. The results suggest that TFH stimulated NK92-MI cells to activate and enhance cytotoxicity of NK92-MI cells.